Modeling international trade flows between CEEC and OECD countries - Christophe Rault; Robert Sova; Anamaria Sova (Center for Economic Studies and ifo Institute (CESifo), 2008)
This article deals with econometric developments for the estimation of gravity model, which allow to get convergent parameter estimates even when a correlation exists between the explanatory variables and the specific unobservable characteristics of each individual. We implement panel data econometric techniques to characterize bilateral trade flows between heterogeneous economies. Our econometric results based on a sample of 4 Central and Eastern European countries (CEEC-4) and 19 OECD countries over a 18-year period highlight the importance by taking into account the unobservable heterogeneity to obtain a robust empirical specification and unbiased coefficients.
Keywords: F13; F15; C23; 330; gravity models; unobservable heterogeneity; panel data models; international trade flows; Internationale Wirtschaftsbeziehungen; Gravitationsmodell; Internationale Arbeitsteilung; Komparativer Kostenvorteil; Osteuropa; OECD-Staaten